KESADARAN HUKUM MAHASISWA PERIHAL KAWASAN TANPA ROKOK DI UNIVERSITAS NEGERI SURABAYA - Andriana, Anita; Purba, Iman Pasu Marganda Hadiarto (Kajian Moral dan Kewarganegaraan, 2025)
This study aims to analyse university students’ legal awareness of Smoke-Free Areas and the factors that influence it. Soekanto’s theory of legal awareness is employed to examine four key indicators, namely knowledge, understanding, attitude, and behaviour. In addition, his framework for factors influencing legal awareness encompasses the law itself, law enforcement, facilities and infrastructure, society, and culture. A descriptive qualitative approach with a case study method was employed. Data were collected through questionnaires using a snowball sampling technique, which yielded 57 respondents. Of these, 28 students were selected for in-depth interviews. The analysis followed the Miles and Huberman model. The findings reveal that students at Universitas Negeri Surabaya demonstrate inadequate legal awareness regarding the Smoke-Free Areas on campus, as reflected in their non-compliant behaviour. This condition is shaped by several contributing factors, including limited policy dissemination, weak supervision, inadequate supporting facilities, ineffective sanctions, peer influence, and the normalisation of smoking on campus. Therefore, strategic efforts are required to enhance legal awareness, including providing education, revising ambiguous regulations, enforcing strict sanctions, improving facilities such as designated smoking areas and monitoring posts, and cultivating a legal culture that supports the internalisation of legal norms in students’ actual behaviour.